Solutions for managing variability in non-invasive brain stimulation studies - Guerra, Andrea; López-Alonso, Virginia; Cheeran, Binith; Suppa, Antonio (Neuroscience letters, 2020)
In the last three decades, a number of non-invasive brain stimulation (NIBS) protocols, capable of assessing and modulating plasticity in the human motor cortex (M1), have been described. For almost as long, NIBS has delivered the tantalising prospect of non-invasive neuromodulation as a therapeutic intervention for neurorehabilitation, psychiatry, chronic pain and other disease states. Apart from modest effects in depression, this early promise has not been realised since the symptomatic improvements produced by NIBS are generally weak. One key factor explaining this lack of clinical translation concerns variability in response to NIBS. Several studies have demonstrated a number of physiological, technical and statistical factors accounting for intra- and inter-subject variability. However, solutions to overcome this problem are still under debate. In the present review, we have provided a detailed description of methodological and technical solutions to control known factors influencing variability. We have also suggested potential strategies to strengthen and stabilize NIBS-induced after-effects. Finally, we propose new possible outcome variables which better reflect intrinsic cortical activity, allowing a more sensitive measurement and valid interpretation of responses to NIBS.